Synthesis of molybdenum disulfide support on carbon for upgrading bio-oil from jatropha residue - Nakapan, Kantapat; Chollacoop, Nuwong; Viriya-Empikul, Nawin; Eiad-Ua, Apiluck (My University, 2017)
Bio-oil or pyrolysis oil can be obtained from fast pyrolysis biomass has several unusual characteristic such as high acid and high oxygen content which cause bio oil not proper to use as a fuel. In this research MoS2 support on carbon material was prepared for the upgrading bio oil via impregnation method on carbon support from biomass. Hydrothermal process which aims to convert biomass into value products. This process usually performed in water and produces the product, namely hydrochar. In this research, bagasse were executed by hydrothermal at 160 °C, 180 °C and 200 °C for 2, 4, 8 and 24 hours each to enhance the porosity of their products. High porosity is well-known desirably for enhancing efficiency of supporting agents since it can load more catalyst quantity. After finishing hydrothermal process, the reactor which carried bagasse was quenching in order to inhibit the reaction inside. Then, the hydrochar was impregnated by MoS2 precursor and carbonized at 450 °C for 2 hours under nitrogen atmosphere to stabilize the metal phase and turned hydrochar into carbon support. MoS2/carbon was characterized by scanning electron microscopy, EDX, FTIR and pyrolyzer gas chromatography/mass spectroscopy.
Keywords: Activated carbon; Bagasse; Carbonization; Hydrothermal; Impregnation; MoS2